Evaluating Business Performance Using The CAMELS Standard An Applied Study On The Microfinance Institution In Syria 2009-2018 - ديوب محمد معن; الرحية رائد (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to evaluate the performance and efficiency of the MFI in Syria and to assess the financial position of the institution and determine its adherence to the international evaluation standards, during the period 2009-2016, and on this basis was applied camels standard, and to address the problem of the subject and test the hypotheses was based on descriptive and analytical approach in The study, in addition to indicators and financial ratios. The study concluded that the Foundation generally adheres to international standards and to keep abreast of current developments and its contribution to the economic system of the State through the work carried out and the financing practiced in the community for small enterprises.